THE ROLE OF INSTAGRAM AS A MARKETING COMMUNICATION MEDIA FOR FASHION THIRFTING SALES - Yulia Sariwaty; Diny Fitriawati; Maya Retnasary (Jurnal Komunikasi dan Bisnis, 2021)
Modernity has changed the social system of society, including marketing communication activities. Advances in communication and information technology support changes in the marketing communication system. Social media facilitates interactive social interaction. Internet technology-based social media also changes the pattern of information dissemination from what was previously one to many audiences to many audiences to many audiences. Thrifting is a term used for sellers of used branded fashion but are still suitable for use. The existence of social media, especially Instagram, is used by Thrift Shops in offering and selling their thrift fashions. Instagram media was deliberately chosen by several Thrift Shops because of the advantages of several features it has in supporting marketing communication activities compared to other social media. Keywords: Instagram, Media, Communication, Marketing